Association of interferon-based therapy with risk of autoimmune diseases in patients with chronic hepatitis C virus infection: A population-based Taiwanese cohort study - Chou, Shu-Ming; Yeh, Hsing-Jung; Lin, Tzu-Min; Chang, Yu-Sheng; Hsu, Hui-Ching; Shen, Yu-Chuan; Kuo, Tzu-Tung; Chen, Jin-Hua; Chen, Shu-Chuan; Chang, Chi-Ching (Frontiers in Immunology, 2022)
Background: Interferon in combination with ribavirin has been the standard of care for chronic hepatitis C virus infection (HCV) for the past few decades. However, its effect on the risk of autoimmune diseases (ADs) among patients with HCV infection remains unclear. We assessed the potential association between interferon-based therapy (IBT) and AD risk in patients with HCV infection. Methods: This retrospective cohort study identified patients diagnosed with HCV infection between January 1, 2006, and December 31, 2015, from Taiwan’s National Health Insurance Research Database. In total, 16,029 patients with HCV infection who received IBT and 141,214 patients with HCV infection who did not receive IBT were included. Both cohorts were followed up to assess the development of ADs. Hazard ratios (HRs) were calculated using the Cox proportional hazards regression model, which was adjusted for potential confounders. Results: The median follow-up period for IBT and non-IBT users was 4.53 and 3.34 years, respectively. No significant difference in the risk of overall ADs (adjusted HR [aHR]: 0.96, 95% confidence interval [CI]: 0.81–1.14) or systemic ADs (aHR: 0.88, 95% CI: 0.71–1.10) was noted during the study period. However, a slight increase in the risk of organ-specific ADs was noted among IBT users (incidence rate ratio: 1.33, 95% CI: 1.02–1.72). Furthermore, analysis of AD subgroups revealed a significant increase in the risks of Graves’ disease (aHR: 6.06, 95% CI: 1.27–28.8) and Hashimoto’s thyroiditis (aHR 1.49, 95% CI 1.01–2.21) among IBT users. Conclusions: IBT use increases the risk of autoimmune thyroid diseases (Graves’ disease and Hashimoto’s thyroiditis) in patients with HCV infection to a greater extent than non-IBT use.